A storm between two waves: Recovery processes, social dynamics, and heterogeneous effects of Typhoon Haiyan on social preferences - Ivo Steimanis; Max Burger; Bernd Hayo; Andreas Landmann; Björn Vollan (Philipps-University Marburg, School of Business and Economics, 2023)
The literature regarding the effects of environmental hazards on social preferences is mixed and partially contradictory. The lack of a baseline in these studies is a severe methodological constraint, as it is hard to identify heterogeneous treatment effects through experience in the recovery process. We exploit a panel of incentivized behavioral measures of solidarity conducted before and after the devastating damages caused by Typhoon Haiyan in the Philippines. We find that Haiyan's impact on individuals' degree of solidarity was non-linear: solidarity was negatively affected in villages with medium damages, whereas no significant impact was observed in those villages that were most and least affected. A potential explanation for this non-linear effect is differences in people's experiences concerning the aid process and help from other villagers. In villages with medium damages, the quality of the aid process and help from other villagers was perceived to be significantly worse than that received by more and less affected villages. Lastly, survey evidence shows that the non-linear effects persist almost 10 years after the disaster.
Keywords: Q54; C93; D91; O12; 330; Social preferences; environmental hazard; natural experiment; social dynamics; Typhoon Haiyan; Philippines